Experimental Investigation on Newtonian Behaviour and Viscosity of TiO2/PVE Nanolubricants for Application in Refrigeration System - Mohd Farid, Ismail; Azmi, Wan Hamzah; Rizalman, Mamat; Hamisa, Abdul Hamid (Semarak Ilmu Publishing, 2022)
The flow characteristics are highly dependent to viscosity of the fluid. For nanolubricant with different concentration, viscosity change is one of important parameter to be measured to evaluate its functional ability as lubricant. This paper studies about the effect of TiO2 nanoparticle in poly vinyl ether (PVE) at different concentration and temperature. Nanolubricant with volume concentration between 0.01% to 0.1% prepared using two-step method and tested at 40°C, 60°C, and 80°C temperature by using digital rheometer. Beforehand, the colloidal suspension fluid was observed by visual and zeta potential measurement to ensure its stability. The fluid Newtonian behaviour was identified for shear rate up to 1000 rpm. The results shown that dynamic viscosity of 0.01% TiO2/PVE nanolubricant had decreased up to 11% for all measured temperature. For other samples, viscosity increment does not reach more than 1.5% compared to pure PVE oil. It also observed that viscosity increment by the increasing of volume concentration, but it decreases by the increment of temperature. The finding in this study confirms that viscosity of TiO2/PVE nanolubricant effected by both temperature and volume concentration to opposite behaviour.